2004
DOI: 10.1592/phco.24.1.150.34803
|View full text |Cite
|
Sign up to set email alerts
|

Liver Function Test Abnormalities and Pruritus in a Patient Treated with Atorvastatin: Case Report and Review of the Literature

Abstract: The 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors (also known as statins) are associated with elevated transaminase levels in 1-3% of patients. Therapy with these drugs requires monitoring of alanine aminotransferase (ALT) levels because animal studies and premarketing clinical trials showed signs of hepatotoxicity that were primarily minor elevations of ALT. Nevertheless, postmarketing experience suggests that hepatotoxicity is rare, and that elevated ALT levels are reversible with continued ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 12 publications
1
11
0
1
Order By: Relevance
“…These patients had average ages > 60 years with a female/male ratio of 2: 1, and 6 out of them had a marked hyperbilirubinemia (> 100 μmol/l). In other 2 cases, one 72-year-old male from Spain and a 71 years old female from USA in the reports of de Castro and Gershovich [10, 11], atorvastatin-induced cholestatic injury was proven by rapid improvement with cessation of the drug and recurrence with re-initiation of atorvastatin. Besides advanced age, hepatic injury appeared associated with systemic diseases and medications.…”
Section: Discussionmentioning
confidence: 99%
“…These patients had average ages > 60 years with a female/male ratio of 2: 1, and 6 out of them had a marked hyperbilirubinemia (> 100 μmol/l). In other 2 cases, one 72-year-old male from Spain and a 71 years old female from USA in the reports of de Castro and Gershovich [10, 11], atorvastatin-induced cholestatic injury was proven by rapid improvement with cessation of the drug and recurrence with re-initiation of atorvastatin. Besides advanced age, hepatic injury appeared associated with systemic diseases and medications.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have demonstrated that statins induce hyperplasia of bile canaliculi, impair bile flow, induce gallstone formation, and elevate serum bile acids and conjugated bilirubin [119]. The incidence of cholestasis, associated with pruritus, jaundice, increased activity of alkaline phosphatase and glutamyltranspeptidase, in statin-treated individuals is about 1/150,000 patient-years [120]. Acute liver failure (ALF) is a life-threatening complication which develops with the incidence of about 1/100,000 patient-years [121].…”
Section: Hepatotoxicitymentioning
confidence: 99%
“…Atorvastatin-related hepatotoxicity has been associated with a mixed pattern of liver injury typically occurring several months after the initiation of the medication. [19][20][21][22] There has also been a recent case report of underlying autoimmune hepatitis apparently revealed by atorvastatin. 23 After broad experience with this medication (hundreds of thousands of treated patients), significantly increased transaminase levels greater than 3 times the upper limit of normal were only seen in 0.7% of cases.…”
Section: Atorvastatinmentioning
confidence: 99%